Clinicopathological and Prognostic Value of Ki-67 Expression in Bladder Cancer: A Systematic Review and Meta-Analysis - Tian, Yuejun; Ma, Zhiming; Chen, Zhaohui; Li, Mingguo; Wu, Zhiping; Hong, Mei; Wang, Hanzhang; Svatek, Robert; Rodriguez, Ronald; Wang, Zhiping (PloS one, 2016)
Ki-67 is an established marker of cell proliferation, and the Ki-67 index correlates with the clinical course of several cancer types, including bladder cancer (BC). However, the clinicopathological and prognostic significance of Ki-67 in bladder cancer remains unclear. Therefore, we performed a systematic review and meta-analysis to clarify this relationship. A comprehensive literature search for relevant studies published up to February 1, 2016, was performed using PubMed, Cochrane Library, Embase and ISI Web of Knowledge. The effects of Ki-67 expression on survival outcome in patients with BC and BC subtypes were evaluated. Furthermore, the relationship between Ki-67 expression and the clinicopathological features of BC were assessed. Thirty-one studies with 5147 bladder cancer patients were selected for evaluation. Ki-67 expression was significantly associated with shorter recurrence-free (HR 1.69, 95% CI: 1.33-2.14), progression-free (HR 1.89, 95% CI: 1.43-2.51), overall (HR 2.03, 95% CI: 1.31-3.16), and cancer-specific (HR 1.69, 95% CI: 1.47-1.95) survival. Moreover, whereas high expression was more common in high tumor stage, recurrence status, tumor size, there was no correlation between high Ki-67 expression and age, gender, smoking habits, and tumor number. Importantly, analysis of the different subgroups of BC suggested that significant correlations between high Ki-67 expression and survival outcome (recurrence-free/progression-free/overall/cancer-specific survival) are present only in European-American patients. The present results indicate that over-expression of Ki-67 is distinctly correlated with poor patient survival. Ki-67 may serve as a valuable biomarker for prognosis in BC patients, particularly in non-Asian BC patients. The results suggest no significant association between Ki-67 expression and BC prognosis in Asian patients. Further efforts are needed to fully clarify this relationship.